2010
DOI: 10.26719/2010.16.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Smoking among male medical sciences students in Semnan, Islamic Republic of Iran

Abstract: We determined the prevalence of smoking among 320 male medical sciences students (174 studying for a medical degree, 95 a bachelor degree and 51 a associate degree) in Semnan, Islamic Republic of Iran. A self-administrated, anonymous questionnaire was used. The prevalence of smoking was 14.4%; 45.6% of the smokers started smoking between the ages of 18 and 20 years, 43.5% starting at university. There was no significant difference in the prevalence between students undertaking different college degrees and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 11 publications
1
17
1
Order By: Relevance
“…Nazary et al investigated the prevalence of cigarette smoking among all male medical sciences students in Semnan, Islamic Republic of Iran [23]. Based on our results, the prevalence of current cigarette smoking among male dental students (26%) was almost twice as high as the prevalence found in that study (14%).…”
Section: ‫ﺍﳌﺘﻮﺳﻂ‬ ‫ﻟﴩﻕ‬ ‫ﺍﻟﺼﺤﻴﺔ‬ ‫ﺍﳌﺠﻠﺔ‬ ‫ﻋﴩ‬ ‫ﺍﻟﺘﺎﺳﻊ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﺜﺎﻣmentioning
confidence: 48%
“…Nazary et al investigated the prevalence of cigarette smoking among all male medical sciences students in Semnan, Islamic Republic of Iran [23]. Based on our results, the prevalence of current cigarette smoking among male dental students (26%) was almost twice as high as the prevalence found in that study (14%).…”
Section: ‫ﺍﳌﺘﻮﺳﻂ‬ ‫ﻟﴩﻕ‬ ‫ﺍﻟﺼﺤﻴﺔ‬ ‫ﺍﳌﺠﻠﺔ‬ ‫ﻋﴩ‬ ‫ﺍﻟﺘﺎﺳﻊ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﺜﺎﻣmentioning
confidence: 48%
“…Although many researches are conducted in different countries, there have been few researches on cigarette smoking in Iran. Nazary et al studied the prevalence of smoking among male students in Semnan University of Medical Sciences, Iran, and found a smoking rate of 14.4% (10). In another study, Ahmadi et al assessed the prevalence of cigarette smoking among students of Shiraz University of Medical Sciences.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that minors in the US (under 18 year of age) smokes too as reported by Silverstein et al [22]. About 4,000 minors start their first cigarette daily, and about 1,000 minors become a daily cigarette smoker [19,24].…”
Section: Introductionmentioning
confidence: 96%
“…Xinguang et al [29] reported that 66.9% of males and 26% of females who are medical students in China smoked cigarettes. A study in Iran medical schools by Nazary et al [19] showed the prevalence of smoking was 14.4% among medical students. For the data to be reliable, and for the sample to provide a proper representation, the sample covered different age groups, different genders, race, occupation, etc.…”
Section: Cigarette Smoking Among Medical Studentsmentioning
confidence: 99%
See 1 more Smart Citation